Effect of fruit alcoholic extract of Myrtus communis Myrtle in growth of some pathogenic bacteria - Dhuha Jasim Mohammed (College of Education for Pure Sciences, 2010)
Abstract This study was effectuate to evaluate the effect of the alcoholic extract of the Myruts communis myrtle fruits on the growth of eight pathogenic bacteria, by used eight different concentrations (3.1, 6.2, 12.5, 25, 50, 100, 200, 400) mg/cm3. Seven from these bacteria were sensitive to the alcoholic extract these are: (Klebsiella pneumonia, Serratia marcescens, Salmonella typhi, Escherichia coli, Bacillus subtilis, pseudomonas aeruginosa and Staphylococcus aureus), whereas Proteus vulgaris were resistant, The results showed an increase in the sensitivity of these genus with the increasing the concentrations of the extract from (6.2) mg/cm3 which is considered the minimum inhibitory concentration M I C, Moreover the other concentrations (12.5, 25, 50, 100, 200, 400) mg/cm3 showed increase which are (18.7%, 138.3%, 514%, 826%, 1081.5%, 1428%) Respectively when compared to the MIC (6.2) mg/cm3 The sensitivity of the examined genus were variable since the diameter inhibition zone (DIZ) were (1.75, 5.4, 5.54, 8.83, 9.08, 11.29, 17.5) respectively.